2017
DOI: 10.15689/ap.2017.1601.08
|View full text |Cite
|
Sign up to set email alerts
|

Assessing stress at work: The Portuguese version of the Job Content Questionnaire

Abstract: The aim of this paper was to study one of the most important tools for assessing the psychosocial factors underlying stress at work. The study of the Portuguese version of the Karasek's Job Content Questionnaire (JCQ) also intends to contribute to the discussion about the theoretical model (the division of the decision latitude in one or two dimensions) and the scale itself (the adequacy of the items from the Psychological Job Demand Scale). Construct validity of the questionnaire was examined using an explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This result is in line with previous studies that showed that psychological demands scale of the JCQ (Karasek, 1985) tends to be the borderline and presenting low satisfactory levels of internal consistency (Choi et al. , 2012; Vilas-Boas and Cerqueira, 2017).…”
Section: Resultssupporting
confidence: 92%
“…This result is in line with previous studies that showed that psychological demands scale of the JCQ (Karasek, 1985) tends to be the borderline and presenting low satisfactory levels of internal consistency (Choi et al. , 2012; Vilas-Boas and Cerqueira, 2017).…”
Section: Resultssupporting
confidence: 92%
“…WDQ is a multidimensional instrument that also assesses areas related to physical risks and comprises 77 items [12]. JCQ is a multidimensional tool of 49 items that operationalizes the job demand-control-support model mentioned above [3], but only 22 items from the full version have been selected for translation into Portuguese [13].…”
Section: Introductionmentioning
confidence: 99%
“…As condições de trabalho podem contribuir para alterações da saúde física e mental dos indivíduos 1 . Quando consideradas as condições e o contexto das atividades executadas no âmbito da saúde, pesquisas realizadas com trabalhadores da área no Brasil evidenciam a existência de associações entre a ocorrência de doenças e transtornos psicossociais com as condições de trabalho desses profissionais 2,3 .…”
Section: Introductionunclassified